Family mediation and sulh: an alternative dispute resolution in Malaysia - Ahmad, Sa'odah; Abdul Hak, Nora (Institut Sosial Malaysia & Faculty of Human Ecology, UPM, 2010)
Mediation and other forms of alternative dispute resolution (ADR) developed rapidly in the era of globalization as an effect of high divorce rates, numerous conflicts between disjointing parents, the consequential administrative burden on courts and especially concerns about detrimental effects on children an post divorce family relationship. An overwhelming change is also taking place in Asia for concurrently with reform in arbitration, the Courts are leading the way to encourage mediation in dispute settlement. This article focuses on the practices of family mediation and sulh in Malaysia and the significance of family mediation and sulh in resolving dispute amicably.